Analysis of Factors Associated with the Risk of Mortality of Covid-19 Patients - Rina Yulimawati; Ning Arti Wulandari; Erni Setiyorini; Ta’adi Ta’adi (Humanistic Network for Science and Technology (HNST), 2023)
Corona disease (Covid-19) has become a global pandemic. In Indonesia, on 2020 there were 3,512 positive cases, with 306 people dying, the mortality rate is 9.1%. East Java has the highest Covid-19 death rate in Indonesia. The aim of this study was to identify the factors associate with the mortality of Covid-19 patients. The present study was conducted based on a retrospective analysis of the medical records of patients hospitalised at Ngudi Waluyo Hospital between March 2020 to September 2021. The study included all cases of patients with a complete medical records data. A total of 1.494 cases were included. The bivariate analysis using Chi-Square Test and univariate by Binary Logistic Regression analysis to evaluate the association between risk factors and mortality. The results showed a relationship between age, gender comobid and comobid classification. The main risk factor of mortality was the presence of comorbidities (p = 0.005; OR = 1,494; 95% CI = 1.132-1.071). The second factor was age (p=0.000; OR=1.419; 95% CI=1.308 – 1.540). Risk factors associated with mortality for patients with Covid-19 in the hospital included advanced age, presence of comorbid and gender. Risk factors of mortality were the presence of comorbidities and age. Keywords: age; gender; comobid; mortality; Covid-19